2002
DOI: 10.1038/sj.gt.3301701
|View full text |Cite
|
Sign up to set email alerts
|

CAR- or αv integrin-binding ablated adenovirus vectors, but not fiber-modified vectors containing RGD peptide, do not change the systemic gene transfer properties in mice

Abstract: Targeted gene delivery to the tissue of interest by recombinant adenovirus (Ad)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 34 publications
(61 reference statements)
2
72
0
1
Order By: Relevance
“…33 However, it has been reported that adenovirus infection is possible without ␣V integrinvirus interaction. [45][46][47] Here, adenovirus was found to be an effective vector to transfer genes into melanoma cells. Based on staining for ␤-galactosidase activity, all cell lines including the ␣V-negative WM-115 cells could be successfully infected with RAdlacZ control virus.…”
Section: Decrease In Cell Surface Expression Of ␣V Integrin Promotes mentioning
confidence: 99%
“…33 However, it has been reported that adenovirus infection is possible without ␣V integrinvirus interaction. [45][46][47] Here, adenovirus was found to be an effective vector to transfer genes into melanoma cells. Based on staining for ␤-galactosidase activity, all cell lines including the ␣V-negative WM-115 cells could be successfully infected with RAdlacZ control virus.…”
Section: Decrease In Cell Surface Expression Of ␣V Integrin Promotes mentioning
confidence: 99%
“…delivery. [4][5][6] Several studies have documented the role of blood coagulation factors in mediating liver gene transfer in vivo and the mechanism underlying Ad5 hepatocyte transduction. [7][8][9][10][11][12] We demonstrated that coagulation factor X (FX) binds to the hexon protein of Ad5 at high affinity (B2 nM) and that this interaction mediates hepatocyte transduction following i.v.…”
mentioning
confidence: 99%
“…delivery. 4,5,19 FX-binding-ablated Ad5 vectors have shown substantially reduced hepatocyte transduction in mice and rats following i.v. delivery.…”
mentioning
confidence: 99%
“…Strategies to inhibit hepatocyte and/or liver Kupffer cell uptake by ablating CAR-or integrin-binding motifs in the Ad capsid have been largely unsuccessful, however, indicating that native Ad tropism determinants contribute little to vector hepatotropism in vivo. [40][41][42][43][44] These data notwithstanding, work by several groups has implicated the fiber protein as a major structural determinant of liver tropism in vivo (reviewed by Nicklin et al 45 ). For example, shortening of the native fiber shaft domain of the Ad5 fiber 46 or replacement of the Ad5 shaft with the short Ad3 shaft domain 47 was shown to attenuate liver uptake in vivo following intravenous delivery.…”
Section: Transductional Targeting Of Admentioning
confidence: 99%